An Analysis of Energy Consumption and CO2 Emission in the Residential Sector: A Case Study of Nonthaburi Province, Thailand - Noppawan Srisatham; Salam, Abdul P.; Dhakal, Shobhakar; Kumar, Sivanappan; Her Majesty the Queen's Scholarships (Pathum Thani, Thailand : Asian Institute of Technology, 2019)
Energy consumption has increased following by rising of population growth rate. It results in increasing of CO2 emission which causes climate change and global warming. In Thailand, energy consumption has risen and residential sector has been the third largest final energy consumption. Moreover, Thai's government has a target to reduce energy intensity by 30% in 2036 according to the Energy Efficiency Development Plan. However, the ministry of transportation in Thailand plans to build sky trains and some of plan is in construction phase which result in rising of condominium and village constructions near sky train routes in Bangkok and metropolitans. Therefore, the appliances market is predicted to increase which causes energy demand rises. In order to reduce energy consumption and CO2 emission, energy efficient are using to replace conventional energy. As Nonthaburi province is one of the metropolitan regions, it has high density of population which can affect to high energy consumption and CO2 emission. This research studies on energy consumption and CO2 emission pattern of residential sector by income levels of Nonthaburi province including high income, medium income and low income. The energy consumption of residential sector consists of electricity consumption, LPG consumption and traditional energy consumption. Based on the consumption pattern and the present trends, the possible opportunities for energy saving and CO2 mitigation are examined. Then, the potential of various efficient options are analyzed which comprise energy saving, CO2 mitigation and payback period. The total annual energy consumption in Nonthaburi province is found to be 15 million GJ. Electricity is the highest consumption which represents 12 million GJ. LPG is the main fuel for cooking, accounting for 2 million GJ. Charcoal, the only one traditional energy that was found in the city, is not used much in the city which results 0.09 GJ. Comparison of energy consumption between three income groups, energy consumption per household is highest in high income group and decreases according to income level. However, total energy consumption is highest in medium income group since the most of households in Nonthaburi province are classified in medium income group. Total CO2 emission in Nothaburi province is approximatelt 1,805 GgC02. According to the fact that C02 emission level directly links with energy consumption level, CO2 is indirectly released from electricity consumption with highest quantity, representing 1,650 GgC02. The direct CO2 emission is from LPG and charcoal consumption which accounts for about 145 and 10 GgC02 respectively. Based on the pattern of energy consumption, the five efficient options are identified for the possible energy saving and CO2 mitigation opportunities. Replacing fluorescent lamp with LED T8 tube can save 153 kWh per household per year of electricity and reduce 50 kgC02 per household per year. It can save high energy and deduct high CO2 emission with the short payback period which is around 1 year and 4 months. However, the efficient options should be selected which appropriate with the households and income levels to get highest efficiency for energy saving and CO2 emission without financial problems.
Thesis (M.Sc.) - Asian Institute of Technology, 2019
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Energy
Keywords: Carbon dioxide emissions -- Environmental effects; Household appliances, Electric -- Energy consumption -- Thailand -- Nonthaburi; Energy consumption -- Thailand -- Nonthaburi